Kewenangan Komisi Pemberantasan Korupsi dalam Penyidikan Kasus Simolator SIM (Kapolri VS KPK) - R. Nazriyah (Fakultas Hukum Universitas Islam Indonesia, 2012)
The research is aimed at finding out which institution, the Corruption Eradication Commission (KPK) or the Indonesian National Police (POLRI), actually has the authority to conduct investigations in the driving simulator case because both institutions stated that they had the authority. This research uses a normative approach supported by legal approach and case study. The type of data is secondary data. The data sources include primary legal materials, secondary legal materials, and tertiary legal materials. The research finding is that according to Law No.30 Year 2002 on Corruption Eradication Commission, Article 50, the Corruption Eradication Commission has the authority to conduct investigations. This authority is also strengthened by the statement of President Susilo Bambang Yudhoyono. To settle the dispute between KPK and POLRI, the President stated in his speech on 8 October 2012 that the driving simulator case involving Inspector General Djoko Susilo should be handled by KPK. Moreover, considering the Memorandum of Understanding among Corruption Eradication Commission, Indonesian National Police, and Attorney General, the authority should be given to KPK.